Pengaruh Corporate Governance (CG) Terhadap Profitabilitas (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Periode 2021-2023) - Aji Saputra; Winarsih, Winarsih (Politeknik Raflesia Press, 2025)
The health of a company can be assessed from the acquisition of profitability through the ROA ratio. To increase company profitability and prevent fraudulent practices requires a good corporate governance component. This study aims to examine the effect of the implementation of corporate governance carried out by the independent board of commissioners, audit committee, managerial ownership, and board of directors on profitability in manufacturing companies in Indonesia. The population in this study are companies in the Chemical Industry, Consumer Goods Industry, and Various Industries sectors that have been listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used purposive sampling and obtained 216 samples. The analysis method used to test the hypothesis is multiple linear regression analysis. The results of this study indicate that the independent board of commissioners, board of directors, and audit committee variables have a positive and significant effect on profitability, while the managerial ownership variable has a negative and significant effect on financial performance in manufacturing companies in Indonesia.